Cyclosporine A Induces Cardiac Developmental Toxicity in Zebrafish by Up-Regulation of Wnt Signaling and Oxidative Stress - Wan, Mengqi; Huang, Ling; Liu, Jieping; Liu, Fasheng; Chen, Guilan; Ni, Huiwen; Xiong, Guanghua; Liao, Xinjun; Lu, Huiqiang; Xiao, Juhua; Tao, Qiang; Cao, Zigang (Frontiers in Pharmacology, 2021)
Due to the widely application of Cyclosporine A (CsA) as an immunosuppressant in clinic, it is necessary to study its potential toxicity. Therefore, we used zebrafish as a model animal to evaluate the toxicity of CsA on embryonic development. Exposure of zebrafish embryos to CsA at concentrations of 5 mg/L, 10 mg/L, and 15 mg/L from 12 hpf to 72 hpf resulted in abnormal embryonic development, including cardiac malformation, pericardial edema, decreased heart rate, decreased blood flow velocity, deposition at yolk sac, shortened body length, and increased distance between venous sinus and arterial bulb (SV-BA). The expression of genes related to cardiac development was disordered, and the apoptotic genes were up-regulated. Oxidative stress level was up-regulated and accumulated in pericardium in a dose-dependent manner. Astaxanthin (ATX) treatment could significantly alleviate zebrafish heart defects. CsA induced up-regulation of Wnt signaling in zebrafish, and IWR-1, an inhibitor of Wnt signaling pathway, could effectively rescue the heart defects induced by CsA. Together, our study indicated that CsA induced cardiac developmental toxicity in zebrafish larvae through up-regulating oxidative stress and Wnt signaling, contributing to a more comprehensive evaluation of the safety of the drug.